Growth of Mycobacterium avium subsp. paratuberculosis, Escherichia coli, and Salmonella Enteritidis during Preparation and Storage of Yogurt. (16th December 2013) - Cirone, K.; Huberman, Y.; Morsella, C.; Méndez, L.; Jorge, M.; Paolicchi, F.
Abstract : The purpose of this study was to determine the viability of Mycobacterium avium subsp. paratuberculosis (MAP), Escherichia coli ( E. coli ), and Salmonella Enteritidis ( S. Enteritidis) during preparation and refrigerated storage of yogurt. Three yogurts were prepared using pasteurized commercial milk. Each yogurt was artificially contaminated with (1) MAP, (2) E. coli + S. Enteritidis, and (3) MAP + E. coli + S. Enteritidis. Samples were taken during and after the fermentation process until day 20 after inoculation. MAP was not detected during their preparation and short-term storage but was recuperated after starting at 180 min after inoculation storage. Live bacterial counts of E. coli, and S. Enteritidis increased during the first 24 hours, followed by a slight decrease towards the end of the study. In this study it was shown how MAP, E. coli, and S. Enteritidis resisted the acidic conditions generated during the preparation of yogurt and low storage temperatures. This work contributes to current knowledge regarding survival of MAP, E. coli, and S. Enteritidis during preparation and refrigerated storage of yogurt and emphasizes the need to improve hygiene measures to ensure the absence of these pathogenic microorganisms in dairy products.